2008
DOI: 10.1016/j.jmb.2008.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of CREB1 and Histone Deacetylase 2 (HDAC2) to the Mouse Ltbp-1 Promoter Regulates its Constitutive Expression in a Dioxin Receptor-dependent Manner

Abstract: Latent TGFbeta-binding protein 1 (LTBP-1) is a key regulator of TGFbeta targeting and activation in the extracellular matrix. LTBP-1 is recognized as a major docking molecule to localize, and possibly to activate, TGFbeta in the extracellular matrix. Despite this relevant function, the molecular mechanisms regulating Ltbp-1 transcription remain largely unknown. Previous results from our laboratory revealed that mouse embryonic fibroblasts (MEF) lacking dioxin receptor (AhR) had increased Ltbp-1 mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 65 publications
3
28
0
Order By: Relevance
“…The promoter analysis done with Mapper database (Marinescu et al, 2005b) showed that all but one of the most highly dysregulated genes had CREM and/or CREB1 binding sites in their promoter regions. Dysregulated pattern of gene expression associated with chronic TCDD exposure is consistent with existing evidence of the AhR involvement in chromatin remodeling (Gomez-Duran et al, 2008;Oesch-Bartlomowicz and Oesch, 2009a;Tian, 2009), potentially in concert with CREB1 in the context of cAMP/PKA signaling (Oesch-Bartlomowicz and Oesch, 2009b;Saeed et al, 2014). Involvement of cAMP/PKA signaling in the AhR signaling pathway has been demonstrated in a number of contexts including central nervous system, reproductive toxicology and wasting syndrome (Landers and Bunce, 1991;Vogel et al, 1998).…”
Section: Discussionsupporting
confidence: 83%
“…The promoter analysis done with Mapper database (Marinescu et al, 2005b) showed that all but one of the most highly dysregulated genes had CREM and/or CREB1 binding sites in their promoter regions. Dysregulated pattern of gene expression associated with chronic TCDD exposure is consistent with existing evidence of the AhR involvement in chromatin remodeling (Gomez-Duran et al, 2008;Oesch-Bartlomowicz and Oesch, 2009a;Tian, 2009), potentially in concert with CREB1 in the context of cAMP/PKA signaling (Oesch-Bartlomowicz and Oesch, 2009b;Saeed et al, 2014). Involvement of cAMP/PKA signaling in the AhR signaling pathway has been demonstrated in a number of contexts including central nervous system, reproductive toxicology and wasting syndrome (Landers and Bunce, 1991;Vogel et al, 1998).…”
Section: Discussionsupporting
confidence: 83%
“…12 Noteworthy, a nuclear-localized constitutively active AHR that blocks gene expression, probably by inducing local epigenetic modifications, has also been previously described. 43,44 Whether the AHR directly binds the p27 KIP1 promoter to repress transcription is not known up-to-now. Alternatively, the AHR may affect p27 KIP1 expression indirectly by modulating other transcription factors, such as HES-1 or c-myc, which are known to inhibit p27 KIP1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that many cytokines and growth factors regulate the efficiency of wound healing Scheid et al, 2000;Singer and Clark, 1999). We focused our attention on TGFβ for several reasons: (1) mouse models with targeted inactivation of the genes encoding β3 integrin (Reynolds et al, 2005) and Dpr2 (Meng et al, 2008) showed accelerated re-epithelialization and an enhanced response to TGFβ, whereas decreased TGFβ activity correlated with impaired wound healing in PKCε-null mice (Leask et al, 2008) and (2) we have extensively shown that absence of AhR expression results in increased TGFβ activity in certain cell types such as fibroblasts and hepatocytes (Corchero et al, 2004;Elizondo et al, 2000;Gomez-Duran et al, 2008a;Gomez-Duran et al, 2006;Santiago-Josefat et al, 2004). Fibroblasts produce many components of the ECM and are also a relevant source of TGFβ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AhR has a role in TGFβ activation because AhR-null mice produce increased levels of active cytokine (Corchero et al, 2004;Elizondo et al, 2000;Gomez-Duran et al, 2008a;Gomez-Duran et al, 2008b;Gomez-Duran et al, 2006;Santiago-Josefat et al, 2004). Based on this information, we performed experiments aimed to analyze the contribution of TGFβ signaling in the AhR-dependent wound-healing phenotype.…”
Section: Tgfβ Signaling Is Increased In Ahrmentioning
confidence: 99%
See 1 more Smart Citation